Educational Technology Approach in Developing a Mind Mapping Based E-Module for Fifth Grade Students at SDN 05 Batu Taba - Sofiati; Fetri Yeni; Jasrial; Ulfia Rahmi (Jurnal Penelitian Pendidikan IPA, 2025)
This study developed and evaluated a Mind Mapping-based e-module as an interactive digital teaching material for the hajj subject in fifth-grade Islamic Religious Education. Using the Research and Development (R&D) method with the ADDIE model, the e-module was designed, produced, and tested for feasibility, practicality, and effectiveness. Expert validation indicated that the product met high feasibility standards, while teacher and student feedback confirmed its practicality in classroom use. Implementation results showed that the e-module effectively enhanced students’ learning motivation and outcomes, supporting active and enjoyable learning in line with the Merdeka Curriculum principles. The findings suggest that the Mind Mapping-based e-module can serve as an innovative solution for integrating technology in elementary Islamic Religious Education, offering a model for developing engaging and student-centered digital teaching materials.